EVALUASI DAN UPAYA PENINGKATAN KINERJA BUNDARAN KALIBANTENG PASCA TERBANGUNNYA FLYOVER - Agustina Maya Paramitha; Radiksa Ivan Sitranata; Bambang Riyanto; YI. Wicaksono (Departemen Teknik Sipil, Fakultas Teknik Universitas Diponegoro, 2013)
The high vehicle passes on Kalibanteng Intersection as one of main road to reach West Semarang area decreasing the traffic performance. One of the strategies to improve the performance is by building a flyover and widening aprroach. The results of the degree of saturation analysis before flyover was build reaches 1,08 on Sudirman Street, 0,92 on Pamularsih Street, 0,71 on Abdulrahman Saleh Street, 0,93 on Siliwangi Street, 1,08 on Bandara Ahmad Yani Street and 0,52 on RE. Martadinata Street. Widening aprroach done by add 2 meters on Siliwangi Street and 4 meters on Sudirman Street. Beside that, also displacing access to Ahmad Yani Airport into Maerokoco. Based on the analysis with widening the aprroach and displacing airport access, road performance is improved, shown by the degree of saturation on Siliwangi Street is less than 0,79, on RE. Martadinata Street less than 0,18, on Sudirman Street less than 0,41, Pamularsih Street less than 0,83 and Abdulrahman Saleh Street less than 0,65. It was concluded that widening the aprroach and displacing airport access produce a better performance than before there is no flyover.